Silica gel for improving UV ray radiation resistance and application thereof

By using dimethylvinyl siloxy-terminated phenyl T-type polydimethylsiloxane and Karstedt catalyst for hydrogen silicon addition reaction, a silicon gel with good light transmission and retention performance was prepared, which solved the problem of light transmittance under UV radiation in the prior art, and achieved higher yellowing resistance and service life.

CN119570036APending Publication Date: 2025-03-07JIAXING UNITED CHEM +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411808126.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the light transmittance of silicon gel under UV radiation, resulting in the problem that the light transmittance of the packaging material will decrease after a long period of radiation.

Method used

A silicon gel with good light transmission and retention properties was prepared by catalyzing the hydrogen addition reaction of platinum vinyl complex (Karstedt catalyst) using dimethylvinyl siloxy-terminated phenyl T-type polydimethylsiloxane as the base polymer.

Benefits of technology

With the extension of UV irradiation time, the silicon gel has a small change in light transmittance, excellent yellowing resistance, and the light transmittance and retention performance can be improved at different phenyl contents, extending its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570036A_ABST
    Figure CN119570036A_ABST
Patent Text Reader

Abstract

The invention discloses a silica gel capable of improving UV (ultraviolet) ray radiation resistance, which is prepared by hydrosilylation reaction of dimethyl vinyl siloxy terminated phenyl T-type polydimethylsiloxane and double-end dimethyl siloxy terminated linear polysiloxane under the action of a catalyst, and the silica gel with good light transmission maintaining performance is prepared. As the UV irradiation time is prolonged, the light transmittance of the prepared silica gel is small in change amplitude, and the anti-yellowing performance is excellent. Meanwhile, the light transmittance retention performance can be further improved along with the increase of the phenyl content when the phenyl content is relatively low and relatively high, so that the influence of the existence of phenyl on the light transmittance retention rate under the same phenyl content is avoided, and the service life is prolonged. The invention also discloses a preparation method of the dimethyl vinyl siloxy-terminated phenyl T-type polydimethylsiloxane and the linear polysiloxane with the double ends terminated by dimethyl siloxy. The method is simple, and the conditions are easy to control. The invention also discloses a preparation method of the dimethyl vinyl siloxy-terminated phenyl T-type polydimethylsiloxane and the linear polysiloxane with the double ends terminated by dimethyl siloxy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a silicone gel with improved UV radiation resistance and application thereof. Background Art

[0002] The rapid development of network information technologies such as 5G technology, Internet of Things, cloud computing and big data has promoted the transformation of touch screen bonding methods to full bonding technology, which has led to the rapid development of liquid optical transparent adhesive OCR (Optical Clear Resin) or LOCA (Liquid Optical Clear Adhesive). Silicone and acrylate are the main materials for liquid OCR / LOCA. Compared with acrylate, silicone materials have stronger universality, more substantial gap filling ability, lower material shrinkage, better yellowing resistance, high temperature resistance, moisture resistance and thermal shock resistance. They are widely used in automotive on-board displays, medical equipment displays and other fields with high requirements for environmental protection testing.

[0003] Conventional silicone materials are composed of polydimethylsiloxane. Compared with methyl, phenyl has a very high molar refractive index. After replacing the methyl group in the dimethyl polysiloxane chain segment with phenyl, the refractive index of polysiloxane can be increased from about 1.4000 to more than 1.5000. This is a very important change for optical packaging materials, which can improve the light extraction efficiency of silicone packaging materials; on the other hand, after replacing the methyl group of the polysiloxane side group with phenyl, the low-temperature flexibility, high-temperature stability and damping performance of polydimethylsiloxane can also be significantly improved with the increase of phenyl content. However, when there are a large number of Si-Ph chain segments in the polysiloxane molecule, as the content of Me2SiO chain segments contained in the polymer molecule decreases, the length of the Me2SiO chain segment is also shortened accordingly. Although the mutual attraction between the two phenyl substituents in the diphenylsiloxane chain segment can effectively enhance the intramolecular and intermolecular interactions, the introduction of phenyl will inevitably lead to a decrease in the flexibility and mobility of the polymer chain, thereby increasing the rigidity of the polymer.

[0004] Since the display device will generate light of different wavelength ranges, especially ultraviolet light with a wavelength below 400nm and high energy, the packaging material is required to withstand UV irradiation, that is, to have the ability to maintain constant light transmittance under UV irradiation. Publication No. CN114933887A discloses a polyorganosiloxane composition resistant to high temperature yellowing, a curing method and a cured product thereof. The composition provided by the present invention includes: component A, component B-1, component B-2, component C, component D, component E and component F; wherein component A is polyorganosiloxane; component B-1 and component B-2 are both polyorganohydrogensiloxane, and have 3 or more hydrogen atoms bonded to silicon atoms in one molecule; component C is MQ silicone resin; component D is a photoactive platinum catalyst; component E is a tackifier; component F is a nitrogen-containing organic compound. However, the cured product prepared by the combination has not been tested for the light transmittance retention effect after UV irradiation.

[0005] Since the benzene ring can absorb the energy of UV rays, the introduction of phenyl groups in silicone materials is considered to be an important way to improve the UV radiation resistance of encapsulation materials in addition to improving the refractive index and light extraction efficiency of encapsulation materials. Therefore, silicone segments containing phenyl groups, such as methylphenylsiloxane segments or diphenylsiloxane segments, are introduced into silicone molecules by copolymerization, in order to achieve the ability of silicone gel to resist UV radiation by using phenyl groups. Reference 1 (Shen Jingbo, Feng Yakai. Recent Advances in Encapsulation Materials for Light Emitting Diodes: A Review. Silicon, 15, 2163-2172, 2023, doi: 10.1007 / s12633-022-02171-y) discloses that phenyl groups are prone to oxidative degradation and produce chromophores under long-term high temperature and radiation environments, resulting in a decrease in the light transmittance of encapsulation materials over time.

[0006] Therefore, it is necessary to find a method for preparing silicone gel with improved light transmittance retention, in order to obtain silicone gel that is more resistant to UV radiation. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a silicone gel with improved UV radiation resistance. The silicone gel uses dimethylvinylsiloxy-terminated phenyl T-type polydimethylsiloxane as the base polymer of the silicone gel, and is obtained by hydrosilylation curing under the action of a platinum vinyl complex (i.e., Karstedt catalyst). The obtained silicone gel has a good light transmission retention effect.

[0008] A silicone gel with improved UV radiation resistance is prepared by a hydrosilylation reaction of a phenyl T-type polydimethylsiloxane terminated with dimethylvinylsiloxy groups and a linear polysiloxane terminated with dimethylsiloxy groups at both ends under the action of a catalyst; the structure of the phenyl T-type polydimethylsiloxane terminated with dimethylvinylsiloxy groups is shown in formula (I):

[0009]

[0010] Wherein, n=0-50; the number average molecular weight of the dimethylvinylsiloxy-terminated phenyl T-type polydimethylsiloxane is 400-11540 g / mol.

[0011] The hydrosilylation reaction uses a polymer containing at least two Si-H functional groups in its molecule (i.e., a crosslinking agent) and another polymer containing at least two Si-CH=CH2 functional groups in its molecule (i.e., a base polymer) as raw materials. Both can be carried out under the catalysis of a platinum vinyl complex (i.e., a Karstedt catalyst) in a temperature range of room temperature to 150°C to obtain a cross-linked cured network with a three-dimensional structure.

[0012] In the present invention, a phenyl T-type polydimethylsiloxane terminated with dimethylvinylsiloxy groups is used as a base polymer instead of a double-end dimethylvinylsiloxy-terminated polydimethylsiloxane to prepare a silicone gel having good light transmission retention performance. The introduction of a phenyl group can increase the refractive index of the polysiloxane and improve the light collection efficiency of the organic silicon encapsulation material. At the same time, there is only one phenyl group on the base polymer, which can effectively control the phenyl content, so that the flexibility and rigidity of the silicone gel are moderate.

[0013] As the UV irradiation time increases, the light transmittance of the silicone gel prepared by the present invention changes slightly and has excellent yellowing resistance. At the same time, the light transmittance retention performance can be further improved with the increase of the phenyl content at both low and high phenyl content, avoiding the influence of the presence of phenyl on the light transmittance retention at the same phenyl content, thereby extending the service life.

[0014] Preferably, the double-end dimethylsiloxy-terminated linear polysiloxane is a double-end dimethylsiloxy-terminated polydimethylsiloxane as shown in structural formula (II) or a double-end dimethylsiloxy-terminated diphenylsiloxy-linked polysiloxane as shown in structural formula (III).

[0015]

[0016] Wherein, n=0-50, and the number average molecular weight of the dual-end dimethylsilyloxy-terminated linear polysiloxane is 330-7750 g / mol.

[0017] Preferably, the molar ratio of the dual-end dimethylsiloxy-terminated linear polysiloxane to the dimethylvinylsiloxy-terminated phenyl T-type polydimethylsiloxane is 0.2-10:1.

[0018] Preferably, the catalyst is a Karstedt catalyst, which is a vinyl complex of platinum, and the total mass ratio of the platinum atom mass to the total mass of the phenyl T-type polydimethylsiloxane terminated with dimethylvinylsiloxy groups and the linear polysiloxane terminated with dimethylsiloxy groups at both ends is 1: (3-100) × 10 -6 .

[0019] The vinyl complex of platinum (i.e., Karstedt catalyst) has a higher reactivity in the hydrosilylation reaction due to the zero-valent platinum in the complex. In the present invention, when the content of platinum atoms is within the above range, the yellowing resistance of the prepared silicone gel can be effectively improved.

[0020] Preferably, an inhibitor is further added to the hydrosilylation reaction, wherein the inhibitor is an acetylene inhibitor, and the mass ratio of the inhibitor to platinum atoms is 10 to 200:1.

[0021] In a specific embodiment of the present invention, 1-ethynyl-1-cyclohexanol is used as an inhibitor. At a relatively low temperature, the inhibitor inhibits the activity of the catalyst by forming a coordination bond with the platinum atom in the Karstedt catalyst, thereby slowing down the rate of the hydrosilylation reaction.

[0022] Preferably, the temperature of the hydrosilylation reaction is 60-180° C., and the reaction time is 1-10 h.

[0023] Preferably, the preparation method of the dimethylvinylsiloxy-terminated phenyl T-type polydimethylsiloxane comprises the following steps: sequentially adding dimethylvinylsilanol lithium and hexamethylcyclotrisiloxane dropwise into anhydrous tetrahydrofuran, heating for reaction, adding phenyltrichlorosilane dropwise into the reaction solution for bridging reaction, and removing impurities to obtain dimethylvinylsiloxy-terminated phenyl T-type polydimethylsiloxane.

[0024] In the present invention, dimethylvinylsiloxy lithium is prepared by non-equilibrium polymerization of hexamethylcyclotrisiloxane initiated by dimethylvinylsilanol lithium, and then dimethylvinylsiloxy lithium is subjected to a bridging reaction with phenyltrichlorosilane to prepare dimethylvinylsiloxy-terminated phenyl T-type polydimethylsiloxane. The specific synthesis route is as follows: Figure 1 As shown, the preparation method is simple and the conditions are easy to control.

[0025] More preferably, the anhydrous tetrahydrofuran is first stirred in a dry, oxygen-free reactor filled with nitrogen, and cooled to -5 to 10°C and maintained for 15 to 120 minutes.

[0026] More preferably, the molar ratio of the lithium dimethylvinylsiliconate to hexamethylcyclotrisiloxane is 0.05-1.00:1.

[0027] In the present invention, the molar ratio of lithium dimethylvinylsilanol and hexamethylcyclotrisiloxane is controlled to obtain dimethylvinylsiloxy chains of different lengths. If the molar ratio is smaller, lithium dimethylvinylsiloxy with a higher degree of polymerization can be obtained.

[0028] More preferably, the heating reaction temperature is 20-50° C., and the reaction time is 6-15 h.

[0029] More preferably, the molar ratio of phenyltrichlorosilane to lithium dimethylvinylsiliconate is 0.3-0.45:1.

[0030] More preferably, the bridging reaction time is 1 to 2 hours.

[0031] Preferably, the preparation method of the diphenylsiloxy chain-bridged polysiloxane terminated with dimethylsiloxy groups at both ends comprises the following steps: sequentially adding dimethylsilanol lithium and hexamethylcyclotrisiloxane dropwise into anhydrous tetrahydrofuran, heating for reaction, adding diphenyldichlorosilane dropwise into the reaction solution for bridging reaction, and obtaining the diphenylsiloxy chain-bridged polysiloxane terminated with dimethylsiloxy groups at both ends after impurities removal.

[0032] In the present invention, dimethylsiloxy lithium is prepared by non-equilibrium polymerization of hexamethylcyclotrisiloxane initiated by dimethylsilanol lithium, and then dimethylsiloxy lithium is reacted with diphenyldichlorosilane to prepare a diphenylsiloxy chain-bridged polysiloxane with double-end dimethylsiloxy end-capped. The specific synthesis route is as follows: Figure 2 As shown, the preparation method is simple and the conditions are easy to control.

[0033] More preferably, the anhydrous tetrahydrofuran is first stirred in a dry, oxygen-free reactor filled with nitrogen, and cooled to -5 to 10°C and maintained for 15 to 120 minutes.

[0034] More preferably, the molar ratio of lithium dimethylsilanol to hexamethylcyclotrisiloxane is 0.075-0.75:1.

[0035] In the present invention, the molar ratio of lithium dimethylsilanol and hexamethylcyclotrisiloxane is controlled to obtain dimethylsiloxy chains of different lengths. If the molar ratio is smaller, lithium dimethylsiloxy with a higher degree of polymerization can be obtained.

[0036] More preferably, the heating reaction temperature is 15-40° C., and the reaction time is 6-15 h.

[0037] More preferably, the molar ratio of phenyltrichlorosilane to lithium dimethylvinylsiliconate is 0.3 to 1:1.

[0038] More preferably, the bridging reaction time is 1 to 2 hours.

[0039] The present invention also provides the use of the silicone gel with improved UV radiation resistance in the preparation of packaging materials. The silicone gel prepared by the present invention has good light transmission retention performance and yellowing resistance performance, which meets the UV radiation resistance required by packaging materials.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] (1) In the present invention, a phenyl T-type polydimethylsiloxane terminated with dimethylvinylsiloxy groups is used as a base polymer instead of a polydimethylsiloxane terminated with dimethylvinylsiloxy groups at both ends to prepare a silicone gel having better resistance to UV radiation. Compared with silicone gel prepared from polydimethylsiloxane, the base polymer used in the present invention contains both vinyl end-capping and phenyl groups. As the UV radiation time increases, the light transmittance of the silicone gel of the present invention changes little, and the yellowing resistance is excellent. The problem of light transmittance decrease after long-term radiation caused by the introduction of phenyl groups can be effectively improved, and the service life is longer.

[0042] (2) The dimethylvinylsiloxy-terminated phenyl T-type polydimethylsiloxane and dimethylvinylsiloxy-terminated phenyl T-type polydimethylsiloxane used in the present invention are both prepared by a non-equilibrium polymerization method, which is simple and the conditions are easy to control. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The invention discloses a specific synthesis route of phenyl T-type polydimethylsiloxane terminated with dimethylvinylsiloxy groups.

[0044] Figure 2 The invention discloses a specific synthetic route of a polysiloxane bridged by diphenylsiloxy chain segments and capped by dimethylsiloxy groups at both ends.

[0045] Figure 3 to Figure 6 They are respectively the phenyl T-type polydimethylsiloxane (PhT-SiVi-19) with n=19 dimethylvinylsiloxy terminated obtained in Preparation Example 2 1 H NMR spectrum, 13 C NMR spectrum, 29 Si NMR spectrum and FT-IR spectrum.

[0046] Figure 7 and Figure 8The methyl T-type polydimethylsiloxane (MeT-SiVi-27) with n=27 obtained in Preparation Example 4 is respectively 1 H NMR spectrum and FT-IR spectrum.

[0047] Figures 9 to 12 The polysiloxane (Ph2O-SiH-18) with n=18 double-terminal dimethylsilyloxy-terminated diphenylsilyloxy chain bridged is prepared in Example 6. 1 H NMR spectrum, 13 C NMR spectrum, 29 Si NMR spectrum and FT-IR spectrum.

[0048] Fig.13 The polydimethylsiloxane (Ph2O-SiVi-7) with n=7 dimethylvinylsiloxy terminated diphenylsiloxy chain bridged was prepared in Example 8. 1 H NMR spectrum.

[0049] Fig.14 The phenyl T-type polydimethylsiloxane (PhT-SiH-9) with n=9 dimethylsilyloxy end-capping prepared in Preparation Example 10 1 H NMR spectrum.

[0050] Fig.15 and Fig.16 The methyl T-type polydimethylsiloxane (MeT-SiH-33) with n=33 and double-end dimethylsilyloxy terminated obtained in Preparation Example 13 1 H NMR spectrum and FT-IR spectrum.

[0051] Fig.17 This is a graph showing the test results of light transmittance retention of the silicone gels prepared in Examples 1 to 3 and Comparative Example 10.

[0052] Fig.18 This is a graph showing the test results of light transmittance retention of the silicone gels prepared in Examples 4 to 6.

[0053] Fig.19 This is a graph showing the test results of light transmittance retention of the silicone gels prepared in Comparative Examples 1 to 5.

[0054] Fig. 20 This is a graph showing the test results of light transmittance retention of the silicone gels prepared in Comparative Examples 6 to 9. DETAILED DESCRIPTION

[0055] The present invention will be further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited to the following examples.

[0056] The raw materials used in the present invention are all commercially available.

[0057] 1 H NMR test: The sample was dissolved in deuterated chloroform (CDCl3) solvent without internal standard and tested using a 400 MHz German Bruker NMR spectrometer (AVANCE II);

[0058] 13 C NMR test: The sample was dissolved in deuterated chloroform (CDCl3) solvent without internal standard and tested using a 500 MHz German Bruker NMR spectrometer (AVANCEⅢ);

[0059] 29 Si NMR test: The sample was dissolved in deuterated chloroform (CDCl3) solvent without internal standard and tested using a 500 MHz German Bruker NMR spectrometer (AVANCEⅢ);

[0060] FT-IR spectrum: The KBr tablet method is used to make the sample into a sample for FT-IR spectrum testing, and the wave number range is 4000~400cm -1 , resolution 4cm -1 ;

[0061] GPC test: PL-GPC50 gel permeation chromatograph was used, with polydimethylsiloxane (U.S. Polymer Standards Company) of known molecular weight as the standard sample, toluene as the mobile phase, flow rate of 1.0 mL / min, column temperature of 35°C, and molecular weight was calculated based on the time it took for the sample to flow out of the chromatographic column relative to the time it took for the standard sample to flow through.

[0062] Dynamic viscosity test: According to GB / T2794-2013 standard, the American Bookfeild DV2TRVTJ0 rotational viscometer was used to measure the viscosity at a constant temperature of 25±0.1℃ and a rotation speed of 200rpm. The test time was 5min, and the uncertainty of the dynamic viscosity was 1%.

[0063] Preparation Example 1: Preparation of n=7 dimethylvinylsiloxy terminated phenyl T-type polydimethylsiloxane (PhT-SiVi-7)

[0064] Add 60 mL of anhydrous tetrahydrofuran (THF) to a 1000 mL three-necked flask that is dry, oxygen-free and nitrogen-filled, place the three-necked flask in an ice bath and start stirring, maintain the temperature at about 0°C for 30 minutes, add 270 mL of THF solution (1 mol / L) of lithium dimethylvinylsilanol to the three-necked flask at a uniform rate over 60 minutes, stir at 0°C for 30 minutes after the addition, then add the prepared THF solution of hexamethylcyclotrisiloxane (dissolve 120 g, 0.54 mol of hexamethylcyclotrisiloxane in 120 mL of anhydrous THF solution) to the three-necked flask at a uniform rate over 60 minutes, then raise the temperature of the reaction mass to 25°C, and continue to react at this temperature for 8 hours. After the reaction is completed, slowly add 20.92 g (0.099 mol, 10% excess) of phenyltrichlorosilane to the three-necked flask and react for 1 hour. After the reaction was completed, the reaction solution was first decompressed to remove low boiling points such as THF, and then LiCl was filtered out under reduced pressure. The filtrate was then distilled under reduced pressure (180°C, -101.1 kPa, 3h) to remove excess phenyltrichlorosilane and other evaporable substances, and 145.56g of the product was collected.

[0065] Taking lithium dimethylvinylsilanol as the key component, the theoretical mass of the product is calculated to be 0.27×101.20+120+0.09×105.19=156.75g, wherein 0.27 is the amount of substance of dimethylvinylsiloxy, 101.20 is the molar mass of dimethylvinylsiloxy; 120 is the mass of the added hexamethylcyclotrisiloxane; 0.09 is the amount of effective substance of silylphenyl functional group, 105.19 is the molar mass of silylphenyl functional group. Based on the theoretical yield and actual yield determined above, the reaction yield is calculated to be (145.56 / 156.75)×100%=92.9%.

[0066] Using polydimethylsiloxane of known molecular weight as the reference substance and toluene as the mobile phase, the number average molecular weight (Mn) of the polymer tested by GPC was 1500 g / mol, the weight average molecular weight (Mw) was 2400 g / mol, and the PDI was 1.57; the viscosity of the polymer tested by a rotational viscometer at 25°C was 16.75 mPa.s; the refractive index of the polymer tested by an Abbe refractometer at 25°C was 1.4200. The polymer was dissolved in deuterated chloroform, and 1,4-dioxane was added as the reference substance for quantitative nuclear magnetic hydrogen spectrum testing. The number of repeated dimethylsiloxy chains on each branch of the polymer was calculated by nuclear magnetic hydrogen spectrum to be 7, the phenyl content was 3.92wt%, and the vinyl content was 1.526×10 -3 mol / g.

[0067] Preparation Example 2: Preparation of n=19 dimethylvinylsiloxy terminated phenyl T-type polydimethylsiloxane (PhT-SiVi-19)

[0068] 30 mL of anhydrous tetrahydrofuran (THF) was added to a 1000 mL three-necked flask that was dry, oxygen-free and nitrogen-filled. The three-necked flask was placed in an ice bath and stirred. The temperature was maintained at about -5°C for 40 min. 107.9 mL of a THF solution (1 mol / L) of lithium dimethylvinylsilanol was uniformly added to the three-necked flask over 45 min. After the addition, the mixture was stirred at -5°C for 60 min. The prepared THF solution of hexamethylcyclotrisiloxane (120 g, 0.54 mol of hexamethylcyclotrisiloxane was dissolved in 120 mL of anhydrous THF solution) was uniformly added to the three-necked flask over 120 min. The temperature of the reaction mass was then raised to 25°C, and the reaction was continued at this temperature for 12 h. After the reaction was completed, 8.53 g (0.04 mol, 10% excess) of phenyltrichlorosilane was slowly added to the three-necked flask and reacted for 1 h. After the reaction was completed, the solution was first decompressed to remove low boiling points such as THF, and then LiCl was filtered out under reduced pressure. The filtrate was then distilled under reduced pressure (180°C, -101.1 kPa, 3h) to remove excess phenyltrichlorosilane and other evaporable substances, and 123.22 g of the product was collected with a yield of 91.4%.

[0069] Using polydimethylsiloxane of known molecular weight as the reference substance and toluene as the mobile phase, the number average molecular weight (Mn) of the polymer tested by GPC was 3300 g / mol, the weight average molecular weight (Mw) was 5500 g / mol, and the PDI was 1.65; the viscosity of the polymer tested by a rotational viscometer at 25°C was 33.75 mPa.s; the refractive index of the polymer tested by an Abbe refractometer at 25°C was 1.4120. The polymer was dissolved in deuterated chloroform, and 1,4-dioxane was added as the reference substance for quantitative nuclear magnetic resonance hydrogen spectrum testing. The number of repeated dimethylsiloxy chains on each branch of the polymer was calculated by nuclear magnetic resonance hydrogen spectrum to be 19, the phenyl content was 1.66wt%, and the vinyl content was 6.47×10 -4 mol / g.

[0070] By the attached Figure 3 It can be seen that δ = 7.26ppm is C D The chemical shift of the proton H in Cl3, δ = 0.05 ~ 0.18 ppm is the -Si-C H The chemical shift of proton H in 3 is between δ=1.50~1.70ppm, and there is -Si-O H And deuterated chloroform contains trace amounts of H The chemical shift of proton H in 2O, δ = 5.71 ~ 6.16ppm is -Si-C H =C HThe chemical shift of the proton H in 2, δ = 7.30 ~ 7.80 ppm is the chemical shift of all the proton H on the benzene ring in -Si-Ph.

[0071] By the attached Figure 4 It can be seen that δ = 76.75ppm is about C Chemical shift of C in DCl3; δ = 0 ~ 1.21ppm is the polymer end group and side chain -Si- C The chemical shift of C atoms in H3, δ = 127.87 ~ 133.63ppm and δ = 139ppm is the chemical shift of C atoms in -Si-Ph, δ = 125ppm and 138ppm is -Si- C H= C Chemical shift of the C atom in H2.

[0072] By the attached Figure 5 It can be seen that δ = -4.11ppm is - Si -CH=CH2 chemical shift of Si atom, δ=-21.94~-20.91ppm is D chain -O- Si The chemical shift of Si atom in (CH3)2-O-, δ=-80.84ppm is about -O3 on T chain Si -Chemical shift of Si atoms in Ph.

[0073] By the attached Figure 6 Visible, wave number 2963cm -1 It is the CH stretching vibration peak in -Si-CH3, with a wave number of 1410 cm -1 It is the stretching vibration peak of -Si-CH=CH2, wave number 1258cm -1 and 787cm -1 It is the characteristic peak of -Si-CH3, wave number 1011cm -1 It is the characteristic peak of Si-O-Si, with a wave number of 666cm -1 It is the characteristic peak of -Si-Ph.

[0074] Preparation Example 3: Preparation of n=28 dimethylvinylsiloxy terminated phenyl T-type polydimethylsiloxane (PhT-SiVi-28)

[0075] Add 20 mL of anhydrous tetrahydrofuran (THF) to a 1000 mL three-necked flask that is dry, oxygen-free and nitrogen-filled, place the three-necked flask in an ice bath and start stirring, maintain the temperature at about 0°C for 45 minutes, add 67.4 mL of THF solution (1 mol / L) of lithium dimethylvinylsilanol to the three-necked flask at a uniform rate over 45 minutes, stir at 0°C for 90 minutes after the addition, then add the prepared THF solution of hexamethylcyclotrisiloxane (dissolve 120 g, 0.54 mol of hexamethylcyclotrisiloxane in 120 mL of anhydrous THF solution) to the three-necked flask at a uniform rate over 90 minutes, then raise the temperature of the reaction mass to 35°C, and continue to react at this temperature for 10 hours. After the reaction is completed, slowly add 5.2 g (0.0246 mol, 10% excess) of phenyltrichlorosilane to the three-necked flask and react for 2 hours. After the reaction was completed, the solution was first decompressed to remove low boiling points such as THF, and then LiCl was filtered out under reduced pressure. The filtrate was then distilled under reduced pressure (180°C, -101.1 kPa, 3h) to remove excess phenyltrichlorosilane and other evaporable substances, and 118.34 g of the product was collected with a yield of 91.6%.

[0076] Using polydimethylsiloxane of known molecular weight as the reference substance and toluene as the mobile phase, the number average molecular weight (Mn) of the polymer was tested by GPC to be 5400 g / mol, the weight average molecular weight (Mw) was 8600 g / mol, and the PDI was 1.60; the viscosity of the polymer at 25°C was tested by a rotational viscometer to be 53.00 mPa.s; the refractive index of the polymer at 25°C was tested by an Abbe refractometer to be 1.4091. The polymer was dissolved in deuterated chloroform, and 1,4-dioxane was added as the reference substance for quantitative nuclear magnetic hydrogen spectrum testing. The number of repeated dimethylsiloxy chains on each branch of the polymer was calculated by nuclear magnetic hydrogen spectrum to be 28, the phenyl content was 1.16wt%, and the vinyl content was 4.52×10 -4 mol / g.

[0077] Preparation Example 4: Preparation of dimethylvinylsiloxy-terminated methyl T-type polydimethylsiloxane (MeT-SiVi-27) with n=27

[0078] Methyltrichlorosilane was used as the bridging agent instead of phenyltrichlorosilane.

[0079] Add 40 mL of anhydrous tetrahydrofuran (THF) to a 1000 mL three-necked flask that is dry, oxygen-free and nitrogen-filled, place the three-necked flask in an ice bath and start stirring, control the temperature to about 0°C, uniformly add 160 mL of a THF solution (1 mol / L) of lithium dimethylvinylsilanol to the three-necked flask, stir at 0°C for 30 min after the addition, then uniformly add the prepared THF solution of hexamethylcyclotrisiloxane (dissolve 290 g, 1.3 mol of hexamethylcyclotrisiloxane in 290 mL of anhydrous THF solution) to the three-necked flask, then raise the temperature of the reaction mass to 25°C, and continue to react at this temperature for 8 h. After the reaction is completed, slowly add 8.97 g (0.06 mol, 10% excess) of methyltrichlorosilane to the three-necked flask for 1 h. After the reaction was completed, the solution was first decompressed to remove low boiling points such as THF, and then LiCl was filtered out under reduced pressure. The filtrate was then distilled under reduced pressure (180°C, -101.1 kPa, 3h) to remove excess phenyltrichlorosilane and other evaporable substances, and 272.56 g of the product was collected with a yield of 88.4%.

[0080] Using polydimethylsiloxane of known molecular weight as the reference substance and toluene as the mobile phase, the number average molecular weight (Mn) of the polymer was tested by GPC to be 8600 g / mol, the weight average molecular weight (Mw) was 13700 g / mol, and the PDI was 1.60; the viscosity of the polymer at 25°C was tested by a rotational viscometer to be 80.75 mPa.s. The polymer was dissolved in deuterated chloroform, and 1,4-dioxane was added as the reference substance for quantitative nuclear magnetic resonance hydrogen spectrum testing. The number of repeated dimethylsiloxy chains on each branch of the polymer was calculated by nuclear magnetic resonance hydrogen spectrum to be 27, the phenyl content was 0wt%, and the vinyl content was 4.72×10 -4 mol / g.

[0081] By the attached Figure 7 It can be seen that δ = 7.26ppm is C D The chemical shift of proton H in Cl3, δ = -0.08 ~ 0.22ppm is the -Si-C H The chemical shift of proton H in 3 is between δ=1.50~1.70ppm, and there is -Si-O H And deuterated chloroform contains trace amounts of H The chemical shift of proton H in 2O, δ = 5.70 ~ 6.17ppm is -Si-C H =C H Chemical shift of proton H in 2.

[0082] By the attached Figure 8 Visible, wave number 2963cm -1 It is the CH stretching vibration peak in -Si-CH3, with a wave number of 1597 cm-1 It is the stretching vibration peak of -Si-CH=CH2, wave number 1258cm -1 and 787cm -1 It is the characteristic peak of -Si-CH3, wave number 1009cm -1 It is the characteristic peak of Si-O-Si.

[0083] Preparation Example 5: Preparation of n=10 double-terminal dimethylsiloxy-terminated diphenylsiloxy-linked polydimethylsiloxane (Ph2O-SiH-10)

[0084] Add 40 mL of anhydrous tetrahydrofuran (THF) to a 500 mL three-necked flask that is dry, oxygen-free and nitrogen-filled, place the three-necked flask in an ice bath and start stirring, maintain the temperature at about 0°C for 30 minutes, add 135 mL of THF solution of lithium dimethylsilanol (1 mol / L) to the three-necked flask at a uniform rate over 60 minutes, stir at 0°C for 30 minutes after the addition, then add the prepared THF solution of hexamethylcyclotrisiloxane (dissolve 60 g, 0.27 mol of hexamethylcyclotrisiloxane in 60 mL of anhydrous THF solution) to the three-necked flask at a uniform rate over 45 minutes, then raise the temperature of the reaction mass to 25°C, and continue to react at this temperature for 8 hours. After the reaction is completed, slowly add 18.8 g (0.0743 mol, 10% excess) of diphenyldichlorosilane to the three-necked flask and react for 1 hour. After the reaction was completed, the solution was first decompressed to remove low boiling points such as THF, and then LiCl was filtered out under reduced pressure. The filtrate was then distilled under reduced pressure (180°C, -101.1 kPa, 3h) to remove excess phenyltrichlorosilane and other evaporable substances, and 69.91 g of the product was collected with a yield of 84.8%.

[0085] Using polydimethylsiloxane of known molecular weight as the reference substance and toluene as the mobile phase, the number average molecular weight (Mn) of the polymer tested by GPC was 1200 g / mol, the weight average molecular weight (Mw) was 1800 g / mol, and the PDI was 1.50; the viscosity of the polymer tested by a rotational viscometer at 25°C was 15.75 mPa.s; the refractive index of the polymer tested by an Abbe refractometer at 25°C was 1.4375. The polymer was dissolved in deuterated chloroform, and 1,4-dioxane was added as the reference substance for quantitative nuclear magnetic hydrogen spectrum testing. The number of repeated dimethylsiloxy chains on each branch of the polymer was calculated by nuclear magnetic hydrogen spectrum to be 10, the phenyl content was 8.48wt%, and the vinyl content was 1.102×10 -3 mol / g.

[0086] Preparation Example 6: Preparation of n=18 double-terminal dimethylsiloxy-terminated diphenylsiloxy-linked polydimethylsiloxane (Ph2O-SiH-18)

[0087] Add 15 mL of anhydrous tetrahydrofuran (THF) to a 500 mL three-necked flask that is dry, oxygen-free and nitrogen-filled, place the three-necked flask in an ice bath and start stirring, maintain the temperature at about 0°C for 45 minutes, add 45 mL of THF solution of lithium dimethylsilanol (1 mol / L) to the three-necked flask at a uniform rate over 30 minutes, stir at 0°C for 60 minutes after the addition, then add the prepared THF solution of hexamethylcyclotrisiloxane (dissolve 60 g, 0.27 mol of hexamethylcyclotrisiloxane in 90 mL of anhydrous THF solution) to the three-necked flask at a uniform rate over 120 minutes, then raise the temperature of the reaction mass to 35°C, and continue to react at this temperature for 10 hours. After the reaction is completed, slowly add 6.27 g (0.0248 mol, 10% excess) of diphenyldichlorosilane to the three-necked flask and react for 1.5 hours. After the reaction was completed, the solution was first decompressed to remove low boiling points such as THF, and then LiCl was filtered out under reduced pressure. The filtrate was then distilled under reduced pressure (180°C, -101.1 kPa, 3h) to remove excess phenyltrichlorosilane and other evaporable substances, and 64.12 g of the product was collected with a yield of 95.0%.

[0088] Using polydimethylsiloxane of known molecular weight as the reference substance and toluene as the mobile phase, the number average molecular weight (Mn) of the polymer tested by GPC was 2500 g / mol, the weight average molecular weight (Mw) was 4800 g / mol, and the PDI was 1.92; the viscosity of the polymer tested by a rotational viscometer at 25°C was 29.25 mPa.s; the refractive index of the polymer tested by an Abbe refractometer at 25°C was 1.4160. The polymer was dissolved in deuterated chloroform, and 1,4-dioxane was added as the reference substance for quantitative nuclear magnetic resonance hydrogen spectrum testing. The number of repeated dimethylsiloxy chains on each branch of the polymer was calculated by nuclear magnetic resonance hydrogen spectrum to be 18, the phenyl content was 5.13wt%, and the vinyl content was 6.66×10 -4 mol / g.

[0089] By the attached Fig. 9 It can be seen that δ = 7.26ppm is C D The chemical shift of the proton H in Cl3, δ = 0.03 ~ 0.19 ppm is the -Si-C H The chemical shift of proton H in 3 is between δ=1.50~1.70ppm, and there is -Si-O H And deuterated chloroform contains trace amounts of H The chemical shift of the proton H in 2O is about δ = 4.68 to 4.72 ppm, which is -Si- HThe chemical shift of the proton H in -Si-Ph is about δ = 7.30 to 7.75 ppm, which is the chemical shift of all the proton H on the benzene ring in -Si-Ph. According to the structural formula and H NMR spectrum of the polymer, due to Si- H There is only one proton H on the -Si-C. If its integral area is defined as 1.00, then H The integrated area of ​​all protons H on 3 is 115.51. From 6n+6=115.51, we can calculate that n≈18, so the molecular weight of the synthesized product is M NMR =3002g / mol.

[0090] By the attached Fig.10 It can be seen that δ = 76.75ppm is about C The chemical shift of C in DCl3, where δ = 0 to 1.05 ppm, is the chemical shift of the polymer end group and side chain -Si- C The chemical shift of C in H3, δ = 127.40 ~ 136.14ppm, is the chemical shift of C in -Si-Ph. Due to the influence of the test environment and the presence of benzene rings in the polymer, the intensity of the C proton peak becomes smaller and the characteristic peak is not obvious. Fig.10 As shown in peak a and peak c.

[0091] By the attached Fig.11 It can be seen that δ = -6.93ppm is Si -H chemical shift of Si atom, δ = -21.95 ~ -20.01ppm is about D chain -O- Si The chemical shift of the Si atom in (CH3)2-O-, δ = -48.49ppm is about -O2 on the D chain Si -Chemical shift of Si atoms in Ph2.

[0092] By the attached Fig.12 Visible, wave number 2963cm -1 It is the CH stretching vibration peak in -Si-CH3, wave number 2127cm -1 -Si-H stretching vibration peak, wave number 1258cm -1 and 787cm -1 It is the characteristic peak of -Si-CH3, wave number 1011cm -1 It is the characteristic peak of Si-O-Si, with a wave number of 696 cm -1 It is the characteristic peak of -Si-Ph.

[0093] Preparation Example 7: Preparation of n=26 double-terminal dimethylsiloxy-terminated diphenylsiloxy-linked polydimethylsiloxane (Ph2O-SiH-26)

[0094] Add 10 mL of anhydrous tetrahydrofuran (THF) to a 500 mL three-necked flask that is dry, oxygen-free and nitrogen-filled, place the three-necked flask in an ice bath and start stirring, maintain the temperature at about 0°C for 60 minutes, add 30 mL of THF solution of lithium dimethylsilanol (1 mol / L) to the three-necked flask at a uniform rate over 45 minutes, stir at 0°C for 90 minutes after the addition, then add the prepared THF solution of hexamethylcyclotrisiloxane (dissolve 60 g, 0.27 mol of hexamethylcyclotrisiloxane in 80 mL of anhydrous THF solution) to the three-necked flask at a uniform rate over 50 minutes, then raise the temperature of the reaction mass to 30°C, and continue to react at this temperature for 12 hours. After the reaction is completed, slowly add 4.18 g (0.0165 mol, 10% excess) of diphenyldichlorosilane to the three-necked flask and react for 2 hours. After the reaction was completed, the solution was first decompressed to remove low-boiling substances such as THF, and then LiCl was filtered out under reduced pressure. The filtrate was then distilled under reduced pressure (180°C, -101.1 kPa, 3h) to remove excess phenyltrichlorosilane and other evaporable substances, and 61.61 g of the product was collected with a yield of 94.8%.

[0095] Using polydimethylsiloxane of known molecular weight as the reference substance and toluene as the mobile phase, the number average molecular weight (Mn) of the polymer was tested by GPC to be 4200 g / mol, the weight average molecular weight (Mw) was 7800 g / mol, and the PDI was 1.86; the viscosity of the polymer at 25°C was tested by a rotational viscometer to be 46.50 mPa.s; the refractive index of the polymer at 25°C was tested by an Abbe refractometer to be 1.4120. The polymer was dissolved in deuterated chloroform, and 1,4-dioxane was added as the reference substance for quantitative nuclear magnetic hydrogen spectrum testing. The number of repeated dimethylsiloxy chains on each branch of the polymer was calculated by nuclear magnetic hydrogen spectrum to be 26, the phenyl content was 3.68wt%, and the vinyl content was 4.78×10 -4 mol / g.

[0096] Preparation Example 8: Preparation of dimethylvinyl terminated diphenylsiloxy chain-bridged polydimethylsiloxane (Ph2O-SiVi-7) with n=7

[0097] Diphenyldichlorosilane was used as the bridging agent instead of phenyltrichlorosilane.

[0098] Add 40 mL of anhydrous tetrahydrofuran (THF) to a 500 mL three-necked flask that is dry, oxygen-free and nitrogen-filled, place the three-necked flask in an ice bath and start stirring, control the temperature to about 0°C, evenly drop 135 mL of a THF solution (1 mol / L) of lithium dimethylvinylsilanol into the three-necked flask, stir at 0°C for 30 min after the addition, then evenly drop the prepared THF solution of hexamethylcyclotrisiloxane (dissolve 60 g, 0.27 mol of hexamethylcyclotrisiloxane in 60 mL of anhydrous THF solution) into the three-necked flask, then raise the temperature of the reaction mass to 25°C, and continue to react at this temperature for 8 h. After the reaction is completed, slowly drop 18.8 g (0.0743 mol, 10% excess) of diphenyldichlorosilane into the three-necked flask for 1 h. After the reaction was completed, the solution was first decompressed to remove low boiling points such as THF, and then LiCl was filtered out under reduced pressure. The filtrate was then distilled under reduced pressure (180°C, -101.1 kPa, 3h) to remove excess phenyltrichlorosilane and other evaporable substances, and 81.42 g of the product was collected with a yield of 94.7%.

[0099] Using polydimethylsiloxane of known molecular weight as the reference substance and toluene as the mobile phase, the number average molecular weight (Mn) of the polymer tested by GPC was 1400 g / mol, the weight average molecular weight (Mw) was 2000 g / mol, and the PDI was 1.45; the viscosity of the polymer tested by a rotational viscometer at 25°C was 16.00 mPa.s; the refractive index of the polymer tested by an Abbe refractometer at 25°C was 1.4372. The polymer was dissolved in deuterated chloroform, and 1,4-dioxane was added as the reference substance for quantitative nuclear magnetic hydrogen spectrum testing. The number of repeated dimethylsiloxy chains on each branch of the polymer was calculated by nuclear magnetic hydrogen spectrum to be 7, the phenyl content was 10.82wt%, and the vinyl content was 1.406×10 -3 mol / g.

[0100] By the attached Fig.13 It can be seen that δ = 7.26ppm is C D The chemical shift of the proton H in Cl3, δ = 0.05 ~ 0.17ppm is the -Si-C H The chemical shift of proton H in 3 is between δ=1.50~1.70ppm, and there is -Si-O H And deuterated chloroform contains trace amounts of H The chemical shift of proton H in 2O is about δ = 5.70 to 6.16 ppm, which is -Si-C H =C H 2, δ = 7.30 ~ 7.80ppm is the chemical shift of all protons H on the benzene ring in -Si-Ph. According to the structural formula and nuclear magnetic hydrogen spectrum of the polymer, due to Si-CH =C H There are three protons H on 2. If its integrated area is defined as 3.00, then -Si-C H The integrated area of ​​all protons H on 3 is 49.28. From 6n+6=49.28, we can calculate that n≈7, so the molecular weight of the synthesized product is M NMR =1423 g / mol.

[0101] Preparation Example 9: Preparation of n=6 dimethylsilyloxy-terminated phenyl T-type polydimethylsiloxane (PhT-SiH-6)

[0102] Dimethylsilyl-terminated phenyl T-type polydimethylsiloxane was prepared by equilibrium polymerization using macroporous cation exchange resin (HND-580) as catalyst.

[0103] 133.48g (0.45mol) of octamethylcyclotetrasiloxane, 49.61g (0.15mol) of 3-dimethylsilyloxy-3-phenyl-1,1,5,5-tetramethyltrisiloxane and 5.00g of HND-580 (the catalyst needs to be dried at 110°C for 3h before use) were added to a 500mL three-necked flask that was dry and oxygen-free and passed with nitrogen. Then the system was heated to 70°C and reacted at this temperature for 8h. After the reaction was completed, the temperature was lowered and the catalyst was filtered to remove the catalyst. The filtrate was subjected to reduced pressure distillation (180°C, -101.1kPa, 3h) to remove low boiling substances, and 136.55g of the product was collected, with a yield of 74.6%.

[0104] Using polydimethylsiloxane of known molecular weight as the reference substance and toluene as the mobile phase, the number average molecular weight (Mn) of the polymer tested by GPC was 1800 g / mol, the weight average molecular weight (Mw) was 7400 g / mol, and the PDI was 4.11; the viscosity of the polymer tested by a rotational viscometer at 25°C was 26.00 mPa.s; the refractive index of the polymer tested by an Abbe refractometer at 25°C was 1.4175. The polymer was dissolved in deuterated chloroform, and 1,4-dioxane was added as the reference substance for quantitative nuclear magnetic resonance hydrogen spectrum testing. The number of repeated dimethylsiloxy chains on each branch of the polymer was calculated by nuclear magnetic resonance hydrogen spectrum to be 6, the phenyl content was 4.62wt%, and the vinyl content was 1.801×10 -3 mol / g.

[0105] Preparation Example 10: Preparation of n=9 dimethylsilyloxy-terminated phenyl T-type polydimethylsiloxane (PhT-SiH-9)

[0106] The preparation method is the same as that of Preparation Example 9, except that the amount of 3-dimethylsilyloxy-3-phenyl-1,1,5,5-tetramethyltrisiloxane added is 33.07 g (0.1 mol), and 143.11 g of product is collected with a yield of 85.9%.

[0107] Using polydimethylsiloxane of known molecular weight as the reference substance and toluene as the mobile phase, the number average molecular weight (Mn) of the polymer tested by GPC was 2300 g / mol, the weight average molecular weight (Mw) was 6600 g / mol, and the PDI was 2.88; the viscosity of the polymer tested by a rotational viscometer at 25°C was 29.50 mPa.s; the refractive index of the polymer tested by an Abbe refractometer at 25°C was 1.4139. The polymer was dissolved in deuterated chloroform, and 1,4-dioxane was added as the reference substance for quantitative nuclear magnetic hydrogen spectrum testing. The number of repeated dimethylsiloxy chains on each branch of the polymer was calculated by nuclear magnetic hydrogen spectrum to be 9, the phenyl content was 3.30wt%, and the vinyl content was 1.286×10 -3 mol / g.

[0108] By the attached Fig.14 It can be seen that δ = 7.26ppm is C D The chemical shift of the proton H in Cl3, δ = 0.02 ~ 0.21ppm is the -Si-C H The chemical shift of proton H in 3 is between δ=1.50~1.70ppm, and there is -Si-O H And deuterated chloroform contains trace amounts of H The chemical shift of proton H in 2O, δ = 4.69 ~ 4.77ppm is -Si- H The chemical shift of the proton H in -Si-Ph is δ = 7.36 ~ 7.62ppm, which is the chemical shift of all the proton H on the benzene ring in -Si-Ph. According to the structural formula and nuclear magnetic hydrogen spectrum of the polymer, due to Si- H There is only one proton H on the -Si-C. If its integral area is defined as 1.00, then H The integral area of ​​all protons H on 3 is 61.13. From 6n+6=61.13, we can calculate that n≈9, so the molecular weight of the synthesized product is M NMR =2333 g / mol.

[0109] Preparation Example 11: Preparation of n=16 dimethylsilyloxy-terminated phenyl T-type polydimethylsiloxane (PhT-SiH-16)

[0110] The preparation method is the same as that of Preparation Example 9, except that the amount of octamethylcyclotetrasiloxane added is 148.31 g (0.5 mol), the amount of 3-dimethylsilyloxy-3-phenyl-1,1,5,5-tetramethyltrisiloxane added is 22.16 g (0.067 mol), and 151.04 g of product is collected with a yield of 88.6%.

[0111] Using polydimethylsiloxane of known molecular weight as the reference substance and toluene as the mobile phase, the number average molecular weight (Mn) of the polymer tested by GPC was 3600 g / mol, the weight average molecular weight (Mw) was 16000 g / mol, and the PDI was 4.41; the viscosity of the polymer tested by a rotational viscometer at 25°C was 60.25 mPa.s; the refractive index of the polymer tested by an Abbe refractometer at 25°C was 1.4103. The polymer was dissolved in deuterated chloroform, and 1,4-dioxane was added as the reference substance for quantitative nuclear magnetic resonance hydrogen spectrum testing. The number of repeated dimethylsiloxy chains on each branch of the polymer was calculated by nuclear magnetic resonance hydrogen spectrum to be 16, the phenyl content was 1.98wt%, and the vinyl content was 7.71×10 -4 mol / g.

[0112] Preparation Example 12: Preparation of dimethylsilyloxy-terminated phenyl T-type polydimethylsiloxane (PhT-SiH-22) with n=22

[0113] The preparation method is the same as that of Preparation Example 11, except that the amount of 3-dimethylsilyloxy-3-phenyl-1,1,5,5-tetramethyltrisiloxane added is 11.02 g (0.033 mol), and 151.04 g of product is collected with a yield of 67.5%.

[0114] Using polydimethylsiloxane of known molecular weight as the reference substance and toluene as the mobile phase, the number average molecular weight (Mn) of the polymer tested by GPC was 4300 g / mol, the weight average molecular weight (Mw) was 28800 g / mol, and the PDI was 6.65; the viscosity of the polymer tested by a rotational viscometer at 25°C was 145.10 mPa.s; the refractive index of the polymer tested by an Abbe refractometer at 25°C was 1.4081. The polymer was dissolved in deuterated chloroform, and 1,4-dioxane was added as the reference substance for quantitative nuclear magnetic hydrogen spectrum testing. The number of repeated dimethylsiloxy chains on each branch of the polymer was calculated by nuclear magnetic hydrogen spectrum to be 22, the phenyl content was 1.47wt%, and the vinyl content was 5.74×10 -4 mol / g.

[0115] Preparation Example 13: Preparation of dimethylsilyloxy-terminated methyl T-type polydimethylsiloxane (MeT-SiH-33) with n=33

[0116] Dimethylsilanol lithium is used instead of dimethylvinylsilanol lithium as the initiator, and methyltrichlorosilane is used instead of phenyltrichlorosilane as the bridging agent.

[0117] Add 10 mL of anhydrous tetrahydrofuran (THF) to a 500 mL three-necked flask that is dry, oxygen-free and nitrogen-filled, place the three-necked flask in an ice bath and start stirring, control the temperature to about 0°C, uniformly add 39 mL of a THF solution (1 mol / L) of lithium dimethylvinylsilanol to the three-necked flask, stir at 0°C for 30 min after the addition, then uniformly add the prepared THF solution of hexamethylcyclotrisiloxane (dissolve 58.41 g, 0.26 mol of hexamethylcyclotrisiloxane in 60 mL of anhydrous THF solution) to the three-necked flask, then raise the temperature of the reaction mass to 25°C, and continue to react at this temperature for 8 h. After the reaction is completed, slowly add 2.14 g (0.014 mol, 10% excess) of methyltrichlorosilane to the three-necked flask for 1 h. After the reaction was completed, the solution was first decompressed to remove low boiling points such as THF, and then LiCl was filtered out under reduced pressure. The filtrate was then distilled under reduced pressure (180°C, -101.1 kPa, 3h) to remove excess phenyltrichlorosilane and other evaporable substances, and 52.07 g of the product was collected with a yield of 84.1%.

[0118] Using polydimethylsiloxane of known molecular weight as the reference substance and toluene as the mobile phase, the number average molecular weight (Mn) of the polymer tested by GPC was 4500 g / mol, the weight average molecular weight (Mw) was 15900 g / mol, and the PDI was 3.53; the viscosity of the polymer tested by a rotational viscometer at 25°C was 74.75 mPa.s. The polymer was dissolved in deuterated chloroform, and 1,4-dioxane was added as the reference substance for quantitative nuclear magnetic resonance hydrogen spectrum testing. The number of repeated dimethylsiloxy chains on each branch of the polymer was calculated by nuclear magnetic resonance hydrogen spectrum to be 33, the phenyl content was 0wt%, and the vinyl content was 3.94×10 -4 mol / g.

[0119] By the attached Fig.15 It can be seen that δ = 7.26ppm is C D The chemical shift of proton H in Cl3, δ = 0.04 ~ 0.19 ppm is the -Si-C H The chemical shift of proton H in 3 is between δ=1.50~1.70ppm, and there is -Si-O H And deuterated chloroform contains trace amounts of H The chemical shift of proton H in 2O, δ = 4.69 ~ 4.77ppm is -Si- H Chemical shift of proton H in the polymer. According to the structural formula and H NMR spectrum of the polymer, due to Si- HThere is only one proton H on the -Si-C. If its integral area is defined as 1.00, then H The integrated area of ​​all protons H on 3 is 204.52. From 6n+6=204.52, we can calculate n≈33, so the molecular weight of the synthesized product is M NMR =7610g / mol.

[0120] By the attached Fig.16 It can be seen that the wave number is 2962cm -1 It is the CH stretching vibration peak in -Si-CH3, wave number 2127cm -1 -Si-H stretching vibration peak, wave number 1258cm -1 and 787cm -1 It is the characteristic peak of -Si-CH3, wave number 1010cm -1 It is the characteristic peak of Si-O-Si.

[0121] Example 1: Preparation of silica gel with a phenyl content of 0.44%

[0122] 1.9780 g of commercially available 1% hydroxylamine with a number average molecular weight of 7200 g / mol and a hydrogen content of 2.76 × 10 -4 mol / g of double-end dimethylhydrogensiloxy-terminated polydimethylsiloxane (purchased from Zhejiang Yingke New Materials Co., Ltd., item number YK-616-79) was mixed evenly with 1.2g of PhT-SiVi-28 obtained in Preparation Example 3, and then 0.016g of Karstedt catalyst with a platinum content of 0.1% and 0.318g of a toluene solution of 1-ethynyl-1-cyclohexanol with a mass fraction of 0.1% were added. After stirring and mixing evenly, the bubbles were removed by vacuum, and the mixture was poured into a 10×10×35mm quartz standard cuvette, and cured at 60°C in a blast drying oven for 5h to prepare an optically transparent silica gel sample. According to the phenyl content in the PhT-SiVi-28 used, the mass fraction of phenyl in the silica gel was calculated to be 0.44%.

[0123] Example 2: Preparation of silica gel with a phenyl content of 0.57%

[0124] 2.0050 g of commercially available 1,2-dihydrogen-containing -4After 0.015 g of Karstedt catalyst with a platinum content of 0.1% and 0.305 g of a toluene solution of 1-ethynyl-1-cyclohexanol with a mass fraction of 0.1% were added, the mixture was stirred and mixed evenly, and the bubbles were removed by vacuum. The mixture was poured into a 10×10×35 mm quartz standard cuvette and cured in a blast drying oven at 120°C for 2 h to prepare an optically transparent silica gel sample. According to the phenyl content in the PhT-SiVi-19 used, the mass fraction of phenyl in the silica gel was calculated to be 0.57%.

[0125] Example 3: Preparation of silica gel with phenyl content of 0.65%

[0126] 3.0030 g of commercially available 1,2-dihydrogen-containing -4 After mixing evenly with 0.6 g of PhT-SiVi-7 obtained in Preparation Example 1, 0.018 g of Karstedt catalyst with a platinum content of 0.1% and 0.36 g of a toluene solution of 1-ethynyl-1-cyclohexanol with a mass fraction of 0.1% were added, and the mixture was stirred and mixed evenly. The bubbles were removed by vacuum and the mixture was poured into a 10×10×35 mm quartz standard cuvette. The mixture was cured in a blast drying oven at 120°C for 2 h to prepare an optically transparent silica gel sample. According to the phenyl content in the PhT-SiVi-7 used, the mass fraction of phenyl in the silica gel was calculated to be 0.65%.

[0127] Example 4: Preparation of silica gel with 3.74% phenyl content

[0128] After uniformly mixing 2.511 g of Ph2O-SiH-26 obtained in Preparation Example 7 and 0.8 g of PhT-SiVi-7 obtained in Preparation Example 1, 0.017 g of Karstedt catalyst with a platinum content of 0.1% and 0.331 g of a toluene solution of 1-ethynyl-1-cyclohexanol with a mass fraction of 0.1% were added, and after stirring and mixing evenly, bubbles were removed by vacuum, and the mixture was poured into a 10×10×35 mm quartz standard cuvette, and cured at 120° C. for 2 h in a blast drying oven to prepare an optically transparent silica gel sample. According to the phenyl content in the raw materials used, the mass fraction of phenyl in the silica gel was calculated to be 3.74%.

[0129] Example 5: Preparation of silica gel with a phenyl content of 4.74%

[0130] After uniformly mixing 2.09 g of Ph2O-SiH-18 obtained in Preparation Example 6 and 1 g of PhT-SiVi-7 obtained in Preparation Example 1, 0.016 g of Karstedt catalyst with a platinum content of 0.1% and 0.309 g of a toluene solution of 1-ethynyl-1-cyclohexanol with a mass fraction of 0.1% were added, and after stirring and mixing evenly, bubbles were removed by vacuum, and the mixture was poured into a 10×10×35 mm quartz standard cuvette, and cured at 120° C. for 2 h in a blast drying oven to prepare an optically transparent silica gel sample. According to the phenyl content in the raw materials used, the mass fraction of phenyl in the silica gel was calculated to be 4.74%.

[0131] Example 6: Preparation of silica gel with 6.65% phenyl content

[0132] 1.931 g of Ph2O-SiH-10 obtained in Preparation Example 5 and 1.3 g of PhT-SiVi-7 obtained in Preparation Example 1 were mixed evenly, and then 0.016 g of Karstedt catalyst with a platinum content of 0.1% and 0.323 g of a toluene solution of 1-ethynyl-1-cyclohexanol with a mass fraction of 0.1% were added. After stirring and mixing evenly, bubbles were removed by vacuum, and the mixture was poured into a 10×10×35 mm quartz standard cuvette, and cured at 120° C. for 2 h in a blast drying oven to prepare an optically transparent silica gel sample. According to the phenyl content in the raw materials used, the mass fraction of phenyl in the silica gel was calculated to be 6.65%.

[0133] Comparative Example 1: Using methyl T-shaped hydrogenated silicone oil as a crosslinking agent to prepare a silicone gel with a phenyl content of 0%

[0134] 1.53 g of MeT-SiH-33 prepared in Preparation Example 13 was mixed with 1.8 g of commercially available MeT-SiH-33 having a viscosity of 97.50 mPa.s at 25°C, Mn=6000 g / mol, and a vinyl content of 1.12×10 -4 After mixing evenly with 0.017 g of Karstedt catalyst with a platinum content of 0.1% and 0.334 g of a toluene solution of 0.1% 1-ethynyl-1-cyclohexanol were added, the mixture was stirred and mixed evenly, and the bubbles were removed by vacuum. The mixture was poured into a 10×10×35 mm quartz standard cuvette and cured at 120°C for 2 h in a forced air drying oven to obtain an optically transparent silica gel sample. According to the phenyl content in the raw materials used, the mass fraction of phenyl in the silica gel was calculated to be 0%.

[0135] Comparative Examples 2 to 10

[0136] The preparation method is the same as that of Comparative Example 1, and the differences are shown in the table below.

[0137] Table 1: Summary of the differences in the preparation methods of Comparative Examples 2 to 10

[0138]

[0139]

[0140] Sample analysis

[0141] The silicone gel samples prepared in Examples 1 to 6 and Comparative Examples 1 to 10 were placed in a UV curing box with a power supply of 2.2 kW and a UV lamp power of 120 mW, and the distance between the sample and the UV lamp was about 10 cm. Each silicone gel sample was irradiated in the UV box for a certain period of time (5 min to 25 min) and then taken out. The transmittance of each UV irradiated sample was tested by an ultraviolet spectrophotometer, and the transmittance of each sample before the UV irradiation experiment was divided by the transmittance of each sample before the UV irradiation experiment was performed to obtain the transmittance retention rate data of each sample. From the data, it can be seen that the different UV light intensities of each silicone gel sample are different.

[0142] Fig.17 The light transmittance retention test result graph of the silicone gels prepared in Examples 1 to 3 and Comparative Example 10 shows that the benzene content of the silicone gels in Comparative Example 10 and Examples 1 to 3 increases from 0% to 0.65% respectively, and the light transmittance retention of the prepared silicone gels shows an overall increasing trend with the increase of the benzene content, indicating that the yellowing resistance of the silicone gel prepared with the vinyl-terminated phenyl T-type structure as the base polymer is enhanced with the increase of the phenyl content.

[0143] Fig.18 This is a test result graph of the transmittance retention of the silicone gel prepared in Examples 4 to 6. Among them, in Examples 4 to 6, since linear dimethylsiloxy-terminated polydimethylsiloxane containing diphenylsiloxy chain segments is used as the Si-H source, the transmittance retention of the prepared silicone gel shows an overall increasing trend as the phenyl content increases from 4.95% to 5.18%, and has good yellowing resistance.

[0144] Fig.19The light transmittance retention test result of the silicone gel prepared in Comparative Examples 1 to 5 is shown in FIG. Among them, the benzene content of the silicone gel in Comparative Examples 1 to 5 increases from 0% to 0.88%, and the light transmittance retention of the prepared silicone gel shows an overall decreasing trend with the increase of the benzene content. Compared with Examples 1 to 3 with the same benzene content of less than 1%, the light transmittance retention of Comparative Examples 1 to 5 has dropped to about 80% at 25 minutes, while Examples 1 to 3 can still maintain about 90%, indicating that under the condition of similar benzene content, the silicone gel prepared using the dimethylvinylsiloxy-terminated phenyl T-type polydimethylsiloxane as the base polymer in the present invention has better light transmittance retention performance.

[0145] Fig. 20 This is a test result graph of the light transmittance retention of the silicone gel prepared in Comparative Examples 6 to 9, wherein the benzene content of the silicone gel in Comparative Examples 6 to 9 increases from 6.53% to 9.65%, and the light transmittance retention of the prepared silicone gel shows an overall decreasing trend with the increase of the benzene content.

[0146] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A silicone gel having improved UV radiation resistance, characterized in that: The silicone gel with improved UV radiation resistance is prepared by a hydrosilylation reaction of a phenyl T-type polydimethylsiloxane terminated with dimethylvinylsiloxy groups and a linear polysiloxane terminated with dimethylsiloxy groups at both ends under the action of a catalyst; the structure of the phenyl T-type polydimethylsiloxane terminated with dimethylvinylsiloxy groups is shown in formula (I): Wherein, n=0-50; the number average molecular weight of the dimethylvinylsiloxy-terminated phenyl T-type polydimethylsiloxane is 400-11540 g / mol.

2. The silicone gel with improved UV radiation resistance according to claim 1, characterized in that: The double-end dimethylsiloxy-terminated linear polysiloxane is a double-end dimethylsiloxy-terminated polydimethylsiloxane as shown in structural formula (II) or a double-end dimethylsiloxy-terminated diphenylsiloxy-linked polysiloxane as shown in structural formula (III). Wherein, n=0-50, and the number average molecular weight of the dual-end dimethylsilyloxy-terminated linear polysiloxane is 330-7750 g / mol.

3. The silicone gel with improved UV radiation resistance according to claim 1, characterized in that: The molar ratio of the double-end dimethylsiloxy-terminated linear polysiloxane to the dimethylvinylsiloxy-terminated phenyl T-type polydimethylsiloxane is 0.2-10:

1.

4. The silicone gel with improved UV radiation resistance according to claim 1, characterized in that: The catalyst is a Karstedt catalyst, which is a vinyl complex of platinum, and the total mass ratio of the platinum atom mass to the total mass ratio of the phenyl T-type polydimethylsiloxane terminated with dimethylvinylsiloxy groups and the linear polysiloxane terminated with double-end dimethylsiloxy groups is 1: (3-100) × 10 -6 .

5. The silicone gel with improved UV radiation resistance according to claim 1, characterized in that: An inhibitor is also added to the hydrosilylation reaction. The inhibitor is an acetylene inhibitor, and the mass ratio of the inhibitor to the platinum atom is 10 to 200:

1.

6. The silicone gel with improved UV radiation resistance according to claim 1, characterized in that: The preparation method of the dimethylvinylsiloxy-terminated phenyl T-type polydimethylsiloxane comprises the following steps: sequentially adding dimethylvinylsilanol lithium and hexamethylcyclotrisiloxane dropwise into anhydrous tetrahydrofuran, heating for reaction, dropping phenyltrichlorosilane into the reaction solution for bridging reaction, and removing impurities to obtain the dimethylvinylsiloxy-terminated phenyl T-type polydimethylsiloxane.

7. The silicone gel with improved UV radiation resistance according to claim 6, characterized in that: The molar ratio of the dimethylvinylsiliconate lithium to hexamethylcyclotrisiloxane is 0.05-1.00:1; the molar ratio of the phenyltrichlorosilane to the dimethylvinylsiliconate lithium is 0.3-0.45:

1.

8. The silicone gel with improved UV radiation resistance according to claim 2, characterized in that: The preparation method of the diphenylsiloxy chain-bridged polysiloxane terminated with dimethylsiloxy groups at both ends comprises the following steps: lithium dimethylsilanol and hexamethylcyclotrisiloxane are sequentially added dropwise into anhydrous tetrahydrofuran, after heating for reaction, diphenyldichlorosilane is added dropwise into the reaction solution for bridging reaction, and after impurities are removed, the diphenylsiloxy chain-bridged polysiloxane terminated with dimethylsiloxy groups at both ends is obtained.

9. The silicone gel with improved UV radiation resistance according to claim 8, characterized in that: The molar ratio of the lithium dimethylsiliconate to hexamethylcyclotrisiloxane is 0.075-0.75:1; the molar ratio of the phenyltrichlorosilane to the lithium dimethylvinylsiliconate is 0.3-1:

1.

10. Use of the silicone gel with improved UV radiation resistance according to any one of claims 1 to 9 in the preparation of packaging materials.

Citation Information

Patent Citations

  • A high-temperature resistant polyorganosiloxane composition, its curing method, and the cured product.

    CN114933887A